Effectiveness of Brewing Time Antioxidant Functional Tea Drink from Forest Plant Leaves Of Sapar (Fordia splendidissima (Miq) Buijsen) - Abdul Rasyid Zarta; Kevin Indrawan; Muhammad Fikri Hernandi; Farida Aryani (Jurnal Loupe, 2024)
radiation, fast food, limited exercise time, stress due to work cannot be avoided, and also from the results of oxidation processes in the body. The development of degenerative diseases caused by free radicals can be inhibited by antioxidant compounds which are able to ward off free radicals. Therefore, the body needs important substances - antioxidants - that help protect it from attacks by free radicals and radical compounds. At certain concentrations, antioxidants can inhibit or slow down the damage caused by oxidative processes. Brewing time has an important role in determining the taste, aroma and active compound content of tea. The need for clear guidance regarding brewing times is becoming increasingly important, especially with the increasing interest in premium tea drinks and the influence of healthy lifestyles. This research aims to know the relationship between brewing time and tea quality in terms of dissolved antioxidant bioactivity content.  This research activity tested the antioxidant activity of Sapar leaf tea with different brewing times, namely 3, 5, 10, 15, 20 and 30 minutes. Antioxidant activity testing uses the DPPH (1,1-Diphenyl-2-picrylhydrazy,) method. From the test results it was found that Sapar leaf tea (Fordia splendidissima (Miq) Buijsen) with a brewing time of 3 minutes had the highest antioxidant bioactivity with a radical inhibition value of 81.46% and the antioxidant bioactivity decreased as the brewing time for the leaf tea became longer.